Estimación de Costos para la Construcción de un Gimnasio Multiuso por Etapas. - Chaves-Gutiérrez, Hugo (Instituto Tecnológico de Costa Rica, 2007)
This project involves the development of detailed cost estimates and inspection of economic gyms type. Through it, seek to create a database containing materials list, activities, and total unit costs, which allows to update the cost of each work by introducing new values and thus have a tool in place. With the completion of this educational project, intended to deliver Costa Rican Institute of Sport and Recreation (ICODER), a format for calculating cost estimates detailed and updated, a gym economic that are commonly requested by the communities. So you give a lot of support to the development of sport in the various communities of our country. Currently, the institution has very limited information concerning budgets sports works, and the project is of great importance to the ICODER.
Proyecto Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2007.
Keywords: Base de datos; Hoja de cálculo; Reducción de costos; Deporte; Paredes de madera; Estructuras de concreto; Presupuesto